Nilai Toleransi Pada Film Semesta Karya Chairun Nissa - Kamilatus Sa'diyah; Khamdun Khamdun; Much Arsyad Fardani (PGSD Universitas Muria Kudus, 2022)
The purpose of this study is to describe the analysis of the value of tolerance in the film Semesta by Chairun Nissa.The research method used is qualitative by using discourse analysis methods. The object of research is the values of tolerance in the Semesta film in thematic learning in elementary schools, where the fifth grade teacher is the facilitator and the informant is the fifth grade students consisting of 6 students, 3 boys and 3 girls. Data analysis uses discourse analysis techniques that focus on two elements, namely first at the word level and secondly how the events and actors involved in an event are about to be discussed.The results of the study show that there are forms of tolerance in Chairun Nissa's universal film, namely respect for Hindus who practice Nyepi, respect for the cultural heritage of gadget rituals, and respect and love for living beings. The value of tolerance in Film Semesta has been implemented and has been implemented, namely introducing the diversity of Indonesia, praying before and after lessons according to their respective beliefs, doing picket together in turns, listening to others when talking without interrupting the conversation, and respecting the personal rights of others.